Temporal Changes in Microbial Communities Beneath Fish Farm Sediments Are Related to Organic Enrichment and Fish Biomass Over a Production Cycle - Quero, Grazia Marina; Ape, Francesca; Manini, Elena; Mirto, Simone; Luna, Gian Marco (Frontiers in Marine Science, 2020)
The marine fish farming industry is growing at a significant rate, yet a number of concerns still remain with regards to environmental impacts on the surrounding coastal sea and its biota. Here, we assessed the impact of intensive farming on benthic prokaryotic communities at a Mediterranean sea bass and sea bream intensive aquaculture site over a period of 10 months, in relation to the increase in fish biomass within the cage together with the organic matter enrichment in the sediments. We report positive relationships between prokaryotic abundance and both organic matter and fish biomass, and a contextual decrease in prokaryotic diversity below the cages. A significant shift in microbial community composition occurred in fish farm sediments (FF) over time, indicating a likely impact of ongoing aquaculture activity on prokaryotic communities. Among the dominant taxa at the impacted site, we found Epsilonproteobacteria and Bacteroidetes, which showed a general increase with fish biomass. Analyses on specialist taxa underlined significant contributions of Clostridiales and Bacteroidales in the farmed sediments. Finally, sea bream and sea bass gut microbiome-related taxa were detected during the sampling period. Our results indicate that prokaryotic community composition underneath the cages is related to fish biomass and organic enrichment over the course of production, and confirms that the study of benthic microbial communities at aquaculture sites represents a useful tool to assess the impact of intensive mariculture on the surrounding environment.